Peran Financial Technology Dalam Membantu UMKM di Tengah Pandemi Covid-19 - Linzzy Pratami Putri; Irma Christiana (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2021)
The Covid-19 pandemic that has hit all parts of the world, including Indonesia, has been going on for more than a year. The pandemic forces us to live by observing strict health protocols, namely maintaining distance, wearing masks, washing hands, avoiding crowds. This causes everything to be done through an online system that is not face-to-face, including in conducting financial transactions. Financial transactions can be easily carried out using fintech (financial technology). Fintech plays an important role in economic transactions in the midst of a pandemic. Fintech technology continues to experience very significant improvements and developments. This study intends to provide an explanation of the role of fintech in helping MSMEs in the midst of a pandemic. The research method used is descriptive qualitative, namely by looking for secondary data sources from research results and news that are discussed and re-explained to get a conclusion. From the discussion, it can be concluded that the role of fintech in helping MSMEs is financial inclusion, sources of financing, and improving MSME financial literacy.